An unusual new fossil genus probably belonging to the Psychopsidae (Neuroptera) from the Eocene Okanagan Highlands, western North America - Makarkin, Vladimir N.; Archibald, S. Bruce (Zootaxa, 2014)
The new genus and species Ainigmapsychops inexspectatus gen. et sp. nov. is described from the early Eocene Okanagan Highlands locality at Republic, Washington, U.S.A. We preliminarily assign it to the Psychopsidae; however, its venation is unusual within this family, particularly by its pectinate branches of AA1 originating at a steep angle, a character state more suggestive of the Osmylidae.